Teachers’ perspectives about learners’ fights: Implications for school Leadership - Sekitla Daniel Makhasane (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
Violence is a global problem. Thousands of people worldwide die daily because of various intentional acts of violence such as collective, interpersonal, and self-directed violence. In South Africa, school violence is escalating. Learner fights are also reportedly increasing in frequency and gravity. In this paper, the researcher reports on the findings of a qualitative study of learner fights in two South African high schools, and the leadership implications thereof. Twelve teachers and two principals were purposely selected and interviewed. The participants perceived learner fights as a complicated phenomenon, especially made complex by the diversity of fight types, fight causes, fights locations within the schools, and the onlookers’ reactions. Notwithstanding responsive management endeavours attempted in the two schools, fights among learners were reported to occur and recur often. The paper contends that there is a need to create an enabling environment where teachers and learners can exercise leadership to dispel learner fights.